Literatur Review : AKUMULASI DAN TOKSISITAS LOGAM BERAT: KADMIUM (Cd), KROMIUM (Cr) DAN NIKEL (Ni) - Devyana Dyah Wulandari; Safinah Izzatunnisa; Derrizkie Divanda Herzhaputra; Ayu Wuryaningrum (POLTEKKES KEMENKES MANADO, 2021)
The action of heavy metals in inhibiting enzymes occurs due to interactions between proteins or enzymes that bind to sulfide groups such as disulfide (-S-S) and sulfhydryl (-SH) in enzymes. The sulfide group is able to bind heavy metals that enter the body and are bound in the blood, because heavy metals have a high affinity for sulfide groups. The bond becomes strong and stable, resulting in increased levels of chromium, cadmium and nickel in the body. This Literature Review study aims to determine the accumulation and dangers caused by exposure to heavy metals chromium (Cr), cadmium (Cd) and Nickel (Ni) in the human body. The literature review research method uses existing research journals in the Google Scholar and PubMed databases with PRISMA Flow guidelines, obtained 10 reference journals for information. The results of the review show that the dangers of exposure to heavy metals chromium (Cr), cadmium (Cd) and nickel (Ni) in the human body can cause toxic effects to the body including kidney failure, lung function, respiratory disorders, skin and cancer.